Protocol for study of financial incentives for smoking cessation in pregnancy (FISCP): randomised, multicentre study - Berlin, Noémi (BMJ Open, 2016)
INTRODUCTION: Maternal smoking during pregnancy is associated with adverse perinatal and postnatal health outcomes. The efficacy of nicotine replacement therapies in helping pregnant smokers to quit is not clearly demonstrated; therefore new interventions should be proposed and assessed. Financial incentives rewarding abstinence from tobacco smoking is one of the promising options. OBJECTIVE: To assess the efficacy of financial incentives on smoking abstinence among French pregnant smokers. METHODS AND ANALYSIS: Participants: pregnant smokers aged ≥18 years, smoking at least five manufactured or three roll-your-own cigarettes per day, and pregnant for <18 weeks of amenorrhoea (WA). Setting: participants will be recruited, included and followed-up at monthly face-to-face visits in 16 maternity wards in France. Interventions: participants will be randomised to a control or an intervention group. After a predefined quit date, participants in the control group will receive €20 vouchers at the completion of each visit but no financial incentive for smoking abstinence. Participants in the intervention group will be rewarded for their abstinence by vouchers on top of the €20 show-up fee. The amount of reward for abstinence will increase as a function of duration of abstinence to stimulate longer periods of abstinence. Main outcome measure: complete abstinence from quit date to the last predelivery visit. Secondary outcome measures: point prevalence abstinence, time to relapse to smoking, birth weight, fetal growth restriction, preterm birth. Main data analysis: outcomes will be analysed on an intention-to-treat (ITT) basis. The ITT population is defined as all randomised smoking pregnant women. ETHICS AND DISSEMINATION: The research protocol was approved by the ethics committee (Comité de Protection des Personnes, CPP) of the Pitié-Salpêtrière Hospital on 15 May 2015, and Amendment No 1 was approved on 13 July 2015. Results will be presented at scientific meetings and published. TRIAL REGISTRATION NUMBER: NCT02606227; Pre-results.